2012
DOI: 10.1016/j.radphyschem.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of γ-radiation on the reactivity of montmorillonite towards H2O2

Abstract: Compacted and water saturated bentonite will be used as an engineered barrier in deep geological repositories for radioactive waste in many countries. Due to the high dose rate of ionizing radiation outside the canisters holding the nuclear waste, radiolysis of the interlayer and pore water in the compacted bentonite is unavoidable. Upon reaction with the oxidizing and reducing species formed by water radiolysis (OH • , e -(aq) , H • , H 2 0 2 , H 2 , H0 2• , H 3 0 + ), the overall redox properties in the bent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Previous studies concerning γ-irradiation of bentonite with low water contents (Huang and Chen, 2004;Negron et al, 2002;Plötze, 2003;Plötze et al, 2002;Pusch et al, 1993;Pushkareva et al, 2002), have only found small or insignificant effects on both the physical and chemical properties of bentonite and montmorillonite, even at very high doses (several MGy, 1 Gy = 1 J/kg). However, in two previous studies, (Holmboe et al, 2011;Holmboe et al, 2009) radiation induced effects manifested as increased structural Fe(II)/FeTot ratio and increased colloid stability, respectively, were found. To the best of our knowledge, no study investigating radionuclide diffusion has yet focused on the effects of ionizing radiation on montmorillonite.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous studies concerning γ-irradiation of bentonite with low water contents (Huang and Chen, 2004;Negron et al, 2002;Plötze, 2003;Plötze et al, 2002;Pusch et al, 1993;Pushkareva et al, 2002), have only found small or insignificant effects on both the physical and chemical properties of bentonite and montmorillonite, even at very high doses (several MGy, 1 Gy = 1 J/kg). However, in two previous studies, (Holmboe et al, 2011;Holmboe et al, 2009) radiation induced effects manifested as increased structural Fe(II)/FeTot ratio and increased colloid stability, respectively, were found. To the best of our knowledge, no study investigating radionuclide diffusion has yet focused on the effects of ionizing radiation on montmorillonite.…”
Section: Introductionmentioning
confidence: 72%
“…The samples were either irradiated under inert (N2) or ambient conditions, either as completely dry or after full water saturation, with or without the presence of 0.1g/L humic substances in the solutions. Since certain radiation induced effects in the montmorillonite such as changes in the structural Fe(II)/Fe(III) ratio (Holmboe et al, 2011) is oxygen sensitive, one set of samples was kept in a glove box with an oxygen concentration of ~5 ppm. Table 1 summarizes the different combinations of sample setups in the batch sorption experiments.…”
Section: Batch Sorption Experimentsmentioning
confidence: 99%
“…Determinations of the ratio between Fe(II) and Fe(III) show that the Fe(II) content increases with dose up to 6.5 kGy [95]. At higher doses, no further increase in Fe(II) content is observed under these conditions.…”
Section: Radiation Effects On the Redox Properties Of Montmorillonitementioning
confidence: 87%
“…The ratio between the two oxidation states can also change the surface charge which could result in changed sorption properties as well as changed stability for colloids produced from montmorillonite. In a recent study [95], the reactivity of γ-irradiated montmorillonite towards H 2 O 2 was investigated. H 2 O 2 is a radiolysis product which is involved in radiation-induced corrosion of copper.…”
Section: Radiation Effects On the Redox Properties Of Montmorillonitementioning
confidence: 99%
“…In recent years, the effects of γ‐irradiation on the colloidal stability of bentonite suspensions,52 the cation adsorption and retention on bentonite,53 and the Fe II /Fe III ratio54 have been studied experimentally. The last property also influences the redox reactivity of the material.…”
Section: Radiation Effects On Bentonite Claymentioning
confidence: 99%